OXIDATIVE STRESS PRODUCTS IN TYPE 2 DIABETES AND THEIR RELATION TO PARAOXONASE 1 ACTIVITY - ABDULQAWI ALI; QAHTAN AHMED; N. H. MANJUNATH (The Bioscan, 2011)
The present study indicated a significant increase in the serum advanced oxidation protein products (AOPP) and malondialdehyde (MDA) a marker of lipid peroxidation, in diabetic group compared to control group. AOPP was found to be positively correlated with MDA and Glycated haemoglobin [HbA1c]. AOPP was negatively correlated with Paraoxonase- 1 (PON1) and this correlation was statistically not significant. PON1 activity was found to be decreased in diabetic group compared to control. Negative correlation was found between PON1activity and MDA, HbA1c and with diabetic period. There was no correlation found between AOPP and diabetic period. On other hand, MDA level was positively correlated with HbA1c and diabetic period. The studies also indicated that there is no difference in the level of AOPP, MDA and PON1 between vegetarian and non-vegetarian subjects. The negative correlation between PON1 level with the levels of MDA, AOPP, HbA1c, and diabetic period indicates the role of PON 1 enzyme in oxidative stress. The positive correlation between the levels of MDA and AOPP supports the coupling process of lipid and protein oxidation